Performance Evaluation of an Anaerobic-Aerobic Biofilter in the Wastewater Treatment System of a Mortuary Facility - I Wayan Sudiyanto; Sri Magfirah HS; Nur Aeni; Sri Misykat Azis; Herlina Sattuang (ARRUS Journal of Engineering and Technology, 2025)
Mortuary facilities generate wastewater with elevated concentrations of organic matter, suspended solids, oils and grease, ammonia, and microbial contaminants, necessitating effective treatment to mitigate environmental and public health risks. This study evaluates the performance of an anaerobic–aerobic biofilter wastewater treatment plant (WWTP) serving a mortuary facility in Makassar City. Wastewater samples were collected at the influent and effluent points of the system during July and August 2025 and analyzed for BOD?, COD, TSS, oil and grease, NH?–N, and total coliforms. The influent wastewater exhibited high pollutant loads (e.g., BOD?: 58.1–58.4 mg/L; COD: 139.50–140.33 mg/L; TSS: 63.2–64.9 mg/L; NH?–N: 13.42–13.94 mg/L; coliforms: 9532–9541 CFU/100 mL). Treatment by the biofilter consistently reduced these contaminants, producing effluent concentrations within applicable national standards. Removal efficiencies in July ranged from 45.56–67.81%, while efficiencies in August ranged from 52.11–70.03% for physicochemical parameters. Microbial removal was also effective, achieving 75.55% and 77.58% reduction in July and August, respectively. These findings demonstrate that the anaerobic–aerobic biofilter performs reliably under routine operating conditions, effectively reducing organic pollutants, suspended solids, oils and grease, ammonia, and total coliforms in mortuary wastewater. The system provides compliant effluent quality without additional treatment stages, indicating its suitability for managing medium-strength, high-organic-load wastewater generated by mortuary activities.